Salivary gland carcinosarcoma in a dog - Almeida, Aliny P.; Malm, Christina; Lavalle, Gleidice; Cassali, Geovanni D.; Santos, Renato L.; Paixão, Tatiane A. (Brazilian Journal of Veterinary Pathology, 2010)
Salivary gland tumors are uncommon in domestic animals, whereas salivary carcinosarcomas are very rare in the dog. A 15-year-old mongrel bitch was diagnosed with carcinosarcoma of the submandibular salivary gland extending into the adjacent muscular tissues and the jugular vein. The tumor displayed two distinct areas, one portion with sarcomatous neoplastic cells with bone and cartilage differentiation, and other areas with a pleomorphic carcinomatous tissue. The epithelial and mesenchymal nature of neoplastic cells were confirmed by immunohistochemistry. Surgery and chemotherapy treatments are discussed.